PEMANFAATAN DATABASE ONLINE EBSCO BAGI PEMUSTAKA - Delvia Gustia Ramayanda (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This research was conducted to determine the use of the Ebsco online database subscribed by the UPT Library of Universitas Negeri Padang for users of the UPT Library of Universitas Negeri Padang. This research method uses a quantitative type of research with a descriptive method. In this study, researchers used two research instruments, namely questionnaire and interview. The questionnaire adapted from Hidayat (2007). This questionnaire has 19 questions divided into four categories namely; frequency of Ebsco online database utilization, purpose of utilization of Ebsco online database, ability of users to browse collections and actions on information search results on Ebsco online databases. From 61 repondents, it can be concluded that users of the Ebsco online database are categorized as